Modelo de gestión administrativa para mejorar la competitividad de la empresa "Wayra Tejidos" - Zambrano, Alexander F. (2019)
The objective of this project was to define an administrative management model to improve the competitiveness of Wayra Tejidos in the city of Otavalo, province of Imbabura. In the elaboration of the investigation the qualitative and quantitative method was applied, logical methods: inductive, deductive, to obtain the primary information was used the techniques of the survey and interviews directed to the human talent of the company. The results of the situational diagnosis in the internal analysis through the AMOFIHT matrix established the strengths and weaknesses of the company. The external analysis made it possible to determine the opportunities and threats of the macro environment through the PESTEL matrix and the micro environment through the matrix of Michael Porter's five competitive forces. The proposal designed the administrative management model from the perspective of organizational development, functional, strategic direction, production strategy, marketing mix strategies, based on criteria of productivity, effectiveness and efficiency, customer satisfaction, with a systematic vision for competitiveness. The actions proposed in the administrative management model to improve competitiveness aim to obtain tangible results, objectives for organizational change, strengthening of production and obtain a greater volume of sales generating innovation and opportunities for improvement to meet the expectations and demands of its customers.